Insect diversity of Sungai Serudong Forest Reserve, Sabah, Malaysia - Razy Japir,; Momin B.,; John L.Y.,; Chung, A.Y.C. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Insect diversity of Sungai Serudong Forest Reserve in Sabah was investigated under the Heart of Borneo programme in Sabah. The nocturnal insect diversity was evaluated by using light-trap from 7:00 p.m. until 9:00 p.m. for three consecutive nights. Diurnal insects were sampled using sweep net. A total of nine insect orders were recorded namely Coleoptera, Hemiptera, Hymenoptera, Isoptera, Lepidoptera, Neuroptera, Odonata, and Phasmida. There were four Bornean endemic species recorded during the survey, namely Chalcosoma moellenkampi (Coleoptera: Scarabaeidae), Aethalida borneana (Lepidoptera: Erebidae), Amata prepuncta (Lepidoptera: Erebidae) and Calvisia sammannani (Phasmida: Diapheromeridae). The mean Shannon Index was 4.00, Simpson Index was 47.76 and Fisher Alpha Index was 83.64. The diversity is considered high, however moderate when compared to other forest reserves in Sabah, Malaysia. This study was able to identify insect communities inside the reserve. It was also able to identify the potential threats affecting the insect diversity. The documented data can serve as baseline information to be used in forest management plan and other relevant research.